Case Report: Infusion-Related Reactions to Intravenous Infliximab and Subcutaneous Ustekinumab in Pediatric Crohn's Disease - Kakiuchi, Toshihiko; Kimura, Sakiko; Esaki, Motohiro; Matsuo, Muneaki (Frontiers in Pediatrics, 2021)
Background: Although the biological agent ustekinumab is reported to be effective for Crohn’s disease in pediatric as well as adult patients, data on the efficacy and safety of ustekinumab in pediatric patients with Crohn’s disease are limited. Here, we describe the case of a pediatric patient who showed an allergic reaction to ustekinumab after subcutaneous maintenance injections but not immediately after initial intravenous injection. Case Presentation: A 9-year-old boy presented to our hospital with diarrhea lasting 2 years and weight loss, leading to the diagnosis of Crohn’s disease. After prednisolone was tapered and discontinued, he promptly relapsed. According to our institution’s protocol, we introduced the biological agent infliximab with premedication. Coughing and vomiting was observed after the second dose of infliximab and it was changed to adalimumab. However, the effect of adalimumab gradually disappeared after 18 months; therefore, it was discontinued and he was treated using ustekinumab. The first intravenous ustekinumab dose was given after administering hydrocortisone, an antiallergic and antipyretic analgesic, as premedication, and no obvious adverse reaction was observed. After 8 weeks, ustekinumab was subcutaneously injected without premedication. The patient then complained of nausea, dizziness, and headache within 15 min of ustekinumab administration. Therefore, for the third dose of ustekinumab, hydrocortisone was administered again as premedication. However, nausea, dizziness, and headache presented 10 min after ustekinumab administration, resulting in discontinuation of further ustekinumab treatment. Conclusion: Careful distinction between “true” infusion-related reactions and anaphylaxis or allergic reactions is necessary to determine whether biological agents can be continued after the development of “so-called” infusion-related reactions. For true infusion-related reactions, it may be possible to continue using the biological agent with appropriate premedication; however, in cases of anaphylaxis, the biological agent itself should be changed.